Novel Demonstration of the Anterior Femoral Cutaneous Nerves using Ultrasound - Pivec, Christopher; Bodner, Gerd; Mayer, Johannes A.; Brugger, Peter C.; Paraszti, Istvan; Moser, Veith; Traxler, Hannes; Riegler, Georg (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose Neuropathy of the intermediate (IFCN) and medial femoral cutaneous nerve (MFCN) is a potential iatrogenic complication of thigh surgery and its diagnosis is limited. This study aimed to evaluate the possibility of the visualization and diagnostic assessment of the IFCN and MFCN with high-resolution ultrasound (HRUS).Materials and Methods In this study, HRUS with high-frequency probes (15 – 22MHz) was used to locate the IFCN and the MFCN in 16 fresh cadaveric lower limbs. The correct identification of the nerves was verified by ink-marking and consecutive dissections at sites correlating to nerve positions (R1 – 3), namely, the origin, the mid portion, and the distal portion, respectively. 12 cases with suspected IFCN and MFCN lesions referred to our clinic for HRUS examinations were also assessed.Results Anatomical dissection confirmed the correct identification of the IFCN in 16/16 branches at all of the different locations (100 %). MFCN was correctly identified at R1 + 3, in all cases (16/16; 100 %), and in 14/16 cases (88 %) at (R2). 12 cases of patients with IFCN and MFCN pathologies (all of iatrogenic origin) were identified. 9 instances of structural damage were visible on HRUS, and all pathologies were confirmed by almost complete resolution of symptoms after selective HRUS-guided blocks with 0.5 – 1 ml lidocaine 2 %.Conclusion This study confirms that the IFCN and the MFCN can be reliably visualized with HRUS throughout the course of these nerves, both in anatomical specimens and in patients.
Keywords: ultrasonography; peripheral nerve; iatrogenic disease; anatomic variation